Space Helping to Complete the Picture - British National Space Centre (BNSC) (London, U.K BNSC, 1996)
This Video Illustrates Companies To Explore for Oil and Minerals, Monitor and Forecast Agricultural Crops, Map Inaccessable Regions of the World, Track Ships and Other Globally Distributed Assets, Monitor and Access the Effects of Pollution using Satellite Derived Data.
Keywords: Artificial Satellites